The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10750-010-0556-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cladoceran assemblages across environmental gradients in Nova Scotia (Canada) lakes

Abstract: Cladocera sub-fossils have widely been recognized as useful environmental indicators. Nevertheless, investigations into the distribution and environmental controls on Cladocera are scarce in North America, hindering their use in paleolimnological studies. Here, we examine cladoceran assemblage and size structure from the surface sediments of 49 soft-water Nova Scotia (Canada) lakes to provide ecological data on this key taxonomic group, the first study of its kind for the northern Atlantic coast of North Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…Cladocera species composition of the dystrophic lakes in the WNP is very similar to that observed in boreal dystrophic lakes at the North Hemisphere [Scandinavia (Rautio 2001;Nevalainen et al 2013), North America (Korosi and Smol 2011), and Russia (Smirnov 1971)]. Our results prove that the studied lakes have much a higher Cladocera species richness than it was previously thought and reported (Kostro 1990, Tunowski 1992, Górniak and Dobrzyń 1999, Karabin 1999.…”
Section: Discussionsupporting
confidence: 86%
“…Cladocera species composition of the dystrophic lakes in the WNP is very similar to that observed in boreal dystrophic lakes at the North Hemisphere [Scandinavia (Rautio 2001;Nevalainen et al 2013), North America (Korosi and Smol 2011), and Russia (Smirnov 1971)]. Our results prove that the studied lakes have much a higher Cladocera species richness than it was previously thought and reported (Kostro 1990, Tunowski 1992, Górniak and Dobrzyń 1999, Karabin 1999.…”
Section: Discussionsupporting
confidence: 86%
“…By collecting and analyzing sediment samples from multiple lakes along defined environmental gradients, researchers have learned a great deal about the ecological requirements of specific species and their usefulness as stress indicators. Examples include investigations in Swiss, Italian, and Austrian alpine lake districts (Lotter et al, 1997;Manca & Armiraglio, 2002;Bigler et al, 2006;Kamenik et al, 2007), Finland (Korhola, 1999;Nevalainen et al, 2011), Canada (Sweetman & Smol, 2006;DeSellas et al, 2008;Korosi & Smol, 2011), Denmark, and the British Isles (Brodersen et al, 1998;Amsinck et al, 2005;Davidson et al, 2007;Kattel et al, 2008, Chen et al, 2010. The data obtained have partly been employed to develop models that are needed to reconstruct reference conditions and long-term histories for the lakes (Korhola et al, 2000(Korhola et al, , 2005Lotter et al, 2000;Amsinck et al, 2006;Davidson et al, 2010a;Nevalainen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the primary forcing factors determining cladoceran distribution vary geographically, recent studies suggested that physical parameters (water depth, altitude, temperature, and ice-cover period) are especially important (Lotter et al, 1997;Korhola, 1999;Amsinck et al, 2006;Sweetman & Smol, 2006;Kamenik et al, 2007;Kattel et al, 2008;Korosi & Smol, 2011). Water chemistry can be influential as well; relationships have been found between cladoceran distribution and pH, nutrients, dissolved organic carbon, and ionic concentration (Bigler et al, 2006;DeSellas et al, 2008;Chen et al, 2010;Korosi & Smol, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent aqueous Ca declines have been accompanied by reduced relative abundances of daphniids (Jeziorski et al, 2008). There is currently little known regarding the Ca demands of chydorids, which are often found in relatively high abundances in softwater lakes (Walseng et al, 2003;Korosi & Smol, 2011), despite the potential insight they may provide regarding the importance of aqueous Ca for cladoceran community composition and distribution.…”
Section: Introductionmentioning
confidence: 99%